Effect of cyclic compression on bone marrow mesenchymal stromal cells in tissue engineered cartilage scaffold. Issue 6 (21st February 2019) - Wang, Wei; Wan, Ying; Fu, Tao; Zhou, Ting; Tang, Xiangyu; Wu, Hua; Liu, Chaoxu; Jagodzinski, Michael
Abstract: In this current study, a novel multilayer porous composite scaffold was fabricated with chitosan (CS), silk fibrin (SF) and nano‐hydroxyapatite (n‐HA). Scanning electron microscope was utilized to detect the characteristics of the composed scaffold. Rat bone marrow stromal cells (rBMSC) were loaded onto the CS/SF/n‐HA scaffold and cultured in a bioreactor under an on–off dynamic compression (10% compressive strain, 0.5 Hz, [2 h action + 4 h pause]/cycle, 4 cycles/day). Metabolism of the loaded rBMSC was assessed through CCK‐8 test. Qualitative polymerase chain reaction and western blot were applied to assess the chondrogenic differentiation of the seeded cells. Compressive modulus of the cell/scaffold constructs was analyzed. Additionally, a pig model was employed to evaluate the effect of the tissue‐engineered cartilage on repairing of cartilage defect. Results showed that the four layers within the scaffold were tightly connected without gaps between porous interfaces of the layers. Scaffold porosity was 92.20% ± 1.30%. The cyclic compression upregulated chondrogenesis markers (Aggrecan, Sox‐9, and collagen II). Increased compressive modulus of the cell/scaffold complex was detected after dynamic compression. The pig bone marrow stromal cells/scaffold complex exposed to cyclic compression presented most favorable reparative effect on the mini pig femoral condyle cartilage defects. Our study suggested that the on–off dynamic compression might be a promising approach to fabricate tissue‐engineered cartilage in vitro . © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1294–1302, 2019.